(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Ecosystem services (ES) are the benefits that people obtain from using ecosystems and can be divided into the following three categories: provisioning, regulating and supporting and cultural services. The strategical importance of ecosystem services is set by the EU Biodiversity Strategy, which put ecosystem services firmly on the EU policy agenda. The aim of the paper is to present and discuss the model for economic (monetary) valuation of ecosystem services for sustainable management of degraded peatlands in Latvia. Based on an economic valuation of ecosystem services (ES), it is possible to compare different territories and different management scenarios. Peatland ecosystems globally represent a major store of soil carbon, a sink for carbon dioxide and a source of atmospheric methane. Climate change may threaten these stocks due to the peat oxidation caused by the draught in areas where the peat extraction has been carried out, as well as the increased risk of forest fires. In Latvia, currently there have not been developed a strategy for the implementation of standard approaches and basic principles for the management of degraded peatlands. There are several options for re-cultivation of degraded peatlands, but for sustainable land use, it is very important to choose the most optimal option from the economic, ecological and society perspective. The research was based on data obtained from a biophysical ES assessment for 28 indicators for 3 scenarios from a 5, 25 and 50-year perspective. The collection of primary data, as well as an aggregation and comparative assessment of secondary data have been carried out by using approbated scientific research methods and ES assessment indicators. The obtained data were adapted to the Latvian socio-economic situation by using correction factors. Depending on ES category, the following assessment methods were used: the market pricing method; the benefit transfer method and the direct market pricing method; the avoided costs method. Economic valuation of peatland re-cultivation scenarios assists land-use planners and policymakers in making ecologically, economically and socio-culturally sustainable land-use decisions, where ecological and economic data are used for a calculated assessment of the land-use options.